2012
DOI: 10.1007/s11596-012-0022-x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro investigation into retention strength and fatigue resistance of various designs of tooth/implant supported overdentures

Abstract: Previously, the choice of prosthetic implant-retained overdentures has depended on data from previous studies about the retention-fatigue strength of the attachment system selected. Little or no data have been available on the correlation between the attachment system selected and the overdenture support configuration. The purpose of the present study was to evaluate the retention force and fatigue resistance of three attachment systems and four support designs of overdenture prosthesis. Four lower edentulous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…Therefore, the aim of this study was to assess information on bite force, QoL, and SEMG during the rehabilitation process of edentulous individuals, replacing their conventional dentures for mandibular implant-supported dentures to assess whether this procedure would benefit them before the new dentures were installed. Different authors have reported results before and after the treatment realization, but none of them collected data during the clinical conduct (Mericske-Stern 1994; Bakke et al 2002;Dellavia et al 2007;Berretin-Felix et al 2008;Emami et al 2009Emami et al , 2015Caloss et al 2011;da Silva et al 2011;Dakhilalian et al 2012Dakhilalian et al , 2014Fatalla et al 2012;Geckili et al 2012b;Mumcu et al 2012;Preciado et al 2012;Awad et al 2014;Cakir et al 2014;De Rossi et al 2014;Boven et al 2015;Mundt et al 2015;Shaghaghian et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the aim of this study was to assess information on bite force, QoL, and SEMG during the rehabilitation process of edentulous individuals, replacing their conventional dentures for mandibular implant-supported dentures to assess whether this procedure would benefit them before the new dentures were installed. Different authors have reported results before and after the treatment realization, but none of them collected data during the clinical conduct (Mericske-Stern 1994; Bakke et al 2002;Dellavia et al 2007;Berretin-Felix et al 2008;Emami et al 2009Emami et al , 2015Caloss et al 2011;da Silva et al 2011;Dakhilalian et al 2012Dakhilalian et al , 2014Fatalla et al 2012;Geckili et al 2012b;Mumcu et al 2012;Preciado et al 2012;Awad et al 2014;Cakir et al 2014;De Rossi et al 2014;Boven et al 2015;Mundt et al 2015;Shaghaghian et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, constant repetitive stress as seen in fatigue test, [8][9][10] permanent deformation can occur.…”
Section: Discussionmentioning
confidence: 99%
“…The placement of dental implants in the optimum strategic position can create a favorable abutment situation, allowing for a variety of new prosthetic anchoring options for a removable prosthesis. 17 This treatment modality offers a viable new option, especially for elderly patients with few remaining functional residual teeth located unilaterally in an appropriate position. 18 In addition, this type of surgical intervention frequently represents minimal encumbrance and minimal invasiveness for those patients.…”
Section: Discussionmentioning
confidence: 99%